Policy Transformation and Law Enforcement in Natural Resources Management: Case Study of Excavation C in Sorong City - Hermanus Way; Hadi Tuasikal; Muh Akhdharisa SJ (JUSTISI, 2025)
This study aims to analyze law enforcement against illegal C excavation mining in Sorong City and identify obstacles during the law enforcement process. The method used is an empirical juridical approach with descriptive analysis. The data sources used primary data obtained through observation, interviews, and document studies, as well as secondary data, which includes primary, secondary, and tertiary legal materials. This study was conducted in the jurisdiction of Southwest Papua, especially Sorong City, using descriptive qualitative analysis. The results show that law enforcement against illegal C excavation mining in Sorong City still faces many obstacles from the local community's regulatory and socio-economic factors. Although there are regulations governing mining, many mining activities occur without official permits, which causes environmental damage. The main barriers are the lack of community legal awareness, weak coordination between related department, and delays in issuing permits that cause illegal mining activities. In addition, this mining activity is often the primary source of income for the community, so strict law enforcement risks increasing poverty and unemployment. In short, law enforcement against illegal C-excavation mining in Sorong City is still not optimal despite regulations. This study provided a new contribution with a participatory approach between the community, government, and industry person to find a balanced solution between environmental sustainability and community economic welfare. Effective law enforcement must be accompanied by community empowerment and better coordination between relevant departments.